SOCIAL MEDIA MARKETING, BRAND ENGAGEMENT, AND PURCHASE INTENTION TOWARD SOMETHINC AMONG YOUNG TIKTOK USERS - Boby Arinto; Rajesh Prettypal Singh; Humairoh Humairoh (Universitas Muhammadiyah Tangerang, 2026)
This study examines how Social Media Marketing Activities (SMMAs) on TikTok influence Consumer Brand Engagement (CBE) and Purchase Intention toward Somethinc, a leading Indonesian beauty brand. It also investigates whether Brand Trust moderates the relationship between CBE and Purchase Intention. The study focuses on TikTok users aged 18-30 years in Greater Jakarta who follow Somethinc and have previously interacted with its content. Data were collected through an online survey using purposive sampling, yielding 150 valid responses. The data were analysed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that all four SMMAS dimensions; entertainment, interactivity, trendiness, and electronic word-of-mouth, significantly enhance Consumer Brand Engagement. In turn, CBE has a strong positive effect on Purchase Intention, while Brand Trust also positively influences Purchase Intention but does not moderate the CBE-Purchase Intention relationship. This study contributes to digital marketing literature by demonstrating the central role of engagement in driving purchase intention among young social-media users, while offering practical insights for beauty brands seeking to optimise TikTok-based marketing strategies.